THE RELATIONSHIP BETWEEN MOTIVATION TO FOLLOW EXTRACURRICULAR SCIENCE WITH PARTICIPATION OF STUDENTS IN THE EXACT LEARNING - Sumiyati, Sumiyati; Fauziah, R Siti Pupu; Makarim, Helwiyah (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research purposes to identify the level of relationship between students’ motivation in learning Sciences through extracurricular activity and their participation in classroom on the subject of Sciences. The object of research is an Islamic Integrated Primary School of Raudlatul Jannah Bogor District in Academic Year of 2014-2015. The method used in this research is a quantitative approach with the sample is all population of students, which takes in 39 students who are participating the extracurricular of Sciences. Furthermore, the technique of data collections is a questionnaire and observation. Additionally, the technique of analysis is Correlation Product Moment’s Pearson. In conclusion, it found that the result of research is shown there is a strong positive relationship between students’ motivation in learning Sciences through extracurricular activity and their participation in classroom on the subject of Sciences by the correlating index of 0,89 which means the relationship between motivation and participation is significant. Thereafter, the result of hypothesis test obtained ttest 11,77 and ttable 2,201 with the standard of significance α=0,05 Besides, the result of determination coefficient test on X variable namely students’ motivation in learning Sciences through extracurricular activity and Y variable namely the participation in classroom on the subject of Sciences obtained 79,21%, which means the motivation on extracurricular activity is contributing the participation on learning Science roughly 79,21% and the rest equally 20,79% is other factors which is contributing regarding students’ participation on learning Sciences in classroom.